2015
DOI: 10.4172/2157-7633.1000314
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Injection of Synovium-Derived Mesenchymal Stem Cells with Hyaluronic Acid Can Repair Articular Cartilage Defects in a Canine Model

Abstract: Objective: The purpose of this study was to evaluate effectiveness of intra-articular injection of synovium-derived mesenchymal stem cells (SMSCs) and hyaluronic acid (HA) for the treatment of articular cartilage defects in a canine model. Methods: Forty-eight knees of 24 beagle dogs were randomly assigned to 16 groups (n=3) according to both the number of injected SMSCs (0.5×10 5 cells, 5×10 6 cells, 5×10 7 cells) and the concentration of HA (0%, 0.01%, 0.1%, 0.5%). A partial-thickness cartilage defect was cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…These results are consistent with those of Miki et al . [ 36 ] study in which a surgically-induced cartilage defect was created in the medial femoral condyle of dogs’ knees. They found marked PGs accumulation and a considerable amount of chondrocyte-like cells after combined intra-articular injection of synovium-derived MSCs and hyaluronic acid 7 weeks postsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of Miki et al . [ 36 ] study in which a surgically-induced cartilage defect was created in the medial femoral condyle of dogs’ knees. They found marked PGs accumulation and a considerable amount of chondrocyte-like cells after combined intra-articular injection of synovium-derived MSCs and hyaluronic acid 7 weeks postsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…The first type and majority of canine OA studies include companion animals suffering from naturally-occurring OA (Tables 1, 2, 3) (28,31,32,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(60)(61)(62). In studies of a second type, joint damage is induced in purpose-bred dogs in order to investigate the potential of MSCs to heal cartilage (Tables 4, 5) (51)(52)(53)(54)(55)(56)(57)(58)(59)63).…”
Section: Types Of Canine Osteoarthritis Research On Mesenchymal Stem mentioning
confidence: 99%
“…In studies based on OA models, cartilage or cranial cruciate ligament defects are created surgically in joints of purpose-bred dogs before MSC administration (51)(52)(53)(54)(55)(56)(57)(58)(59)63). In some studies, however, MSCs are administered during or immediately after surgery, which might not adequately represent the effect on chronic OA (52,53,(56)(57)(58).…”
Section: Types Of Canine Osteoarthritis Research On Mesenchymal Stem mentioning
confidence: 99%
“…While in vitro studies provide a substantial amount of information about the potential of MSCs for cartilage repair, evaluation of the in vivo behavior and function of these cells is also required. In vivo studies of cMSCs for cartilage regeneration have involved the use of surgically induced cartilage defect models, including partial-thickness cartilage defect models[62,85-87] (Figure 4A), full-thickness cartilage defect models[88,89] (Figure 4B) and cranial cruciate ligament transection models[90]. (Table 3) In every model, intraarticular autologous[86-88] or allogeneic[51,63,89] cMSC injection demonstrated excellent regenerative effects, including hyaline-like cartilage regeneration, when compared with control groups.…”
Section: In Vivo Study Of Cartilage Regeneration With Cmscsmentioning
confidence: 99%
“…Some studies have demonstrated greater repair effects, determined by histological evaluation of chondral defects, for intraarticular injections of cMSCs in combination with either hyaluronic acid[63,88] or platelet-rich plasma[90] when compared with injection of cMSCs alone. Therefore, some synergistic effects of cMSCs are expected when used in combination with chondroprotective materials.…”
Section: In Vivo Study Of Cartilage Regeneration With Cmscsmentioning
confidence: 99%